Combined complementary imaging techniques in morphological analysis of Spongilla lacustris (Linnaeus 1759). (3rd February 2023) - Woźnica, Andrzej; Karczewski, Jerzy; Gwiazda, Robert; Karcz, Jagna; Bernaś, Tytus; Libera, Marcin; Babczyńska, Agnieszka; Łozowski, Bartosz
Abstract: Sponges, like Spongilla lacustris, as filter feeders, play an essential role in water purification in aquatic ecosystems . The body of this demosponge, in general, consists of both organic soft skeleton and a siliceous scaffold. Their construction of the spicule‐bundling scaffold as mechanical support for skeletal organic mesohyl seems crucial for filtration efficiency. Understanding the structure of the sponge's biosilica‐based scaffold as well as its location within three‐dimensional (3D) skeletal construct requires the introduction of effective analytical methods. The investigations focused on the morphology and architecture of skeletal elements of S. lacustris utilizing the combination of X‐ray computed microtomography ( μ CT) and scanning electron microscopy with energy‐dispersive X‐ray spectroscopy (SEM/EDS). The construction details, surface morphology and chemical composition of the sponge scaffold are presented. μ CT provided the reconstructed 3D images of skeleton structures, including longitudinally and transversely oriented bundles of overlapping spicules, forming a ladder‐like construction as well as the length, geometric distribution, and the surface of the spicules. Further analyses based on SEM/EDS confirmed the proper identification of the structures and their localization and revealed a high abundance of silicon and a low amount of carbon and oxygen in spicules, high abundance of silicon, carbon and oxygen in layered membranes surrounding the bundles of spicules but predominating carbon in the pinacoderm. Combination of these techniques provides a unique image of the sponge body morphology. Verified set of tools may be used for further analyses of sponge body mechanics.